A generalized index of market power (2005)
This paper analyses two approaches to measuring market power -the commonly used Lerner index and a range of exploitation measures-. It is argued that the Lerner index is designed to quantify market power from the supply side, and the exploitation measures are designed to quantify market power from the demand side, and that those two approaches do not always behave in a symmetric way, since they do not always have the same bounds. To sort out these potentially undesirable properties, this paper proposes a new general index to measure market power, which is symmetrical in the sense that it is bounded between cero and one, regardless of whether the market power comes from the supply or the demand side. The index proposed allows for the presence of more than one firm and for the existence of conjectural variations.